Dinamika Tim dan Kolaborasi Antar Sub Bagian Dalam Konteks Bisnis Modern Di PTPN III - Saing, Chairul Nazar; Suhairi, Suhairi (CV. Kalimasada Group, 2023)
In the context of contemporary business, this study investigates inter-subdivision collaboration and team dynamics at PTPN III. Effective team dynamics are mainly shaped by open communication, consistent leadership, and cross-functional collaboration, according to the results of qualitative and quantitative approaches. Even with initiatives to improve cooperation, subdivisions still need strategic measures to strengthen their cooperation, such as the establishment of forums for collaboration and the integration of information systems. It has been shown that the utilization of technology and information systems supports operational efficiency, and that the development of team skills is critical to improving production. These findings also emphasize the importance of fostering an innovative culture that encourages experimentation and measured risk-taking. In addition, a more comprehensive performance review could provide a more accurate representation of each sub-section's contribution. Combining these data, this study concludes that PTPN III's readiness to deal with changing business conditions can be improved through strategic actions to enhance team dynamics and collaboration between sub-sections, such as improving communication, strengthening collaboration, and encouraging innovation.